Chemical structure and mechanical properties of soda lime silica glass surfaces treated by thermal poling in inert and reactive ambient gases. Issue 7 (16th February 2018) - Luo, Jiawei; Bae, Stephen; Yuan, Mengxue; Schneider, Erik; Lanagan, Michael T.; Pantano, Carlo G.; Kim, Seong H.
Abstract: This study employed thermal poling at 200°C as a means to modify the surface mechanical properties of soda lime silica (SLS) glass. SLS float glass panels were allowed to react with molecules constituting ambient air (H2 O, O2, N2 ) while sodium ions were depleted from the surface region through diffusion into the bulk under an anodic potential. A sample poled in inert gas (Ar) was used for comparison. Systematic analyses of the chemical composition, thickness, silicate network, trapped molecular species, and hydrous species in the sodium‐depleted layers revealed correlations between subsurface structural changes and mechanical properties such as hardness, elastic modulus, and fracture toughness. A silica‐like structure was created in the inert gas environment through restructuring of Si–O–Si bonds at 200°C in the Na‐depleted zone; this occurred far below Tg. This silica‐like surface also showed enhancement of hardness comparable to that of pure silica glass. The anodic thermal poling condition was found so reactive that O2 and N2 species can be incorporated into the glass, which also alters the glass structure and mechanical properties. In the case of the anodic surfaces prepared in a humid environment, the glass showed an improved resistance against crack formation, which implies that abundant hydrous species incorporated during thermal poling could be beneficial to improve the toughness.